Capacitor placement in distribution systems, a new formulation - Shwehdi, M.H. (2003)
Two formulations of capacitor placement problem (CPP) are presented. One is based on capacitors/losses cost balance. The other is based on comprehensive cost evaluation of network performance post CP. GA based program is implemented to solve CPP. Proposed solution technique is tested on 69-bus system reported in the literature. In addition, impact of capacitor installation on fault level and network resonance is investigated.